Sustainable Forest Management from Hydrology and Climate Change Mitigation Perspectives - Widiyatno Widiyatno; Chay Asdak (Jurnal Ilmu Kehutanan, 2023)
The increasing number of hydrometeorological disasters induced by unsustainable landscape management has led to significant fatalities and economic loss. Forest ecosystem landscapes are strategic national capital that could contribute to climate change mitigation. The government had formulated policies on Folu Net Sink 2030 through sustainable forest management, environmental and carbon governance, and a Nationally Determined Contribution (NDC) strategic approach using its natural infrastructure in the form of forest ecosystem landscapes. The government could establish attractive and integrated incentive and disincentive systems and mechanisms with sustainable forest management to achieve the targets.